Incidence of Complications Following Thermocautery-assisted Circumcisions - Tuncer, Ahmet Ali; Deger, Mutlu (Urology Journal, 2018)
Purpose: This study aimed to examine the short- and long-term complications of thermocautery-assisted circumcisions. Materials and Methods: A total of 1780 children who consecutively underwent thermocautery-assisted circumcisions from May 2014 to May 2016 in Yuksekova State Hospital in Turkey were included in this study. Thesechildren were classified into perioperative, early postoperative, and long-term complication groups. In addition, the age groups were compared in terms of complications. Results: The patient age and surgical duration means were 4.16 ± 3.805 years old and 6.14 ± 1.703 minutes, respectively. Complications were observed in twelve patients, or 0.6% of the whole observation set. One patient exhibited bleeding and was included in the perioperative complications group. Four patients were included in the early postoperative complications group; three of them had bleeding and one had an infection. Finally, three patients had trapped penises, two patients had meatitis, one patient had a delayed wound healing issue, and one had a glans-skin bridge. These seven patients fell into the long-term complications group. The patients younger than 3 years old had significantly higher complication rates when compared to the older patients, and this comparison was statistically significant (P = 0.001). Conclusion: The results showed that thermocautery-assisted circumcision is a safe and efficient surgical technique for use in children.